An Unexpected Double Diels–Alder Reaction of (E)‐2‐Bromo‐4‐aryl‐1, 3‐pentadiene Involving [1, 5]‐Hydrogen Migration and HBr Elimination: Synthesis of Bicyclo[2.2.2]octene Derivatives. Issue 3 (23rd January 2015) - Huang, Pingping; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract An unexpected double Diels–Alder (DDA) reaction of (E)‐2‐bromo‐4‐aryl‐1, 3‐pentadiene was developed and resulted in a series of "butterfly‐like" bicyclo[2.2.2]octene derivatives in moderate to good yields without the need for a metal catalyst. The proposed mechanism involves a [1, 5]‐sigmatropic hydrogen migration and HBr elimination. Through this decisive [1, 5]‐hydrogen shift step, the electronic properties and steric hindrance of the conjugated diene substrate are completely altered and the DDA reaction of this potential diene synthon is successfully achieved.